Regulation of Substantia Nigra Pars Reticulata GABAergic Neuron Activity by H2O2 via Flufenamic Acid-Sensitive Channels and KATP Channels - Lee, Christian R.; Witkovsky, Paul; Rice, Margaret E. (Frontiers in Systems Neuroscience, 2011)
Substantia nigra pars reticulata (SNr) GABAergic neurons are key output neurons of the basal ganglia. Given the role of these neurons in motor control, it is important to understand factors that regulate their firing rate and pattern. One potential regulator is hydrogen peroxide (H2O2), a reactive oxygen species that is increasingly recognized as a neuromodulator. We used whole-cell current clamp recordings of SNr GABAergic neurons in guinea-pig midbrain slices to determine how H2O2 affects the activity of these neurons and to explore the classes of ion channels underlying those effects. Elevation of H2O2 levels caused an increase in the spontaneous firing rate of SNr GABAergic neurons, whether by application of exogenous H2O2 or amplification of endogenous H2O2 through inhibition of glutathione peroxidase with mercaptosuccinate. This effect was reversed by flufenamic acid, implicating transient receptor potential (TRP) channels. Conversely, depletion of endogenous H2O2 by catalase, a peroxidase enzyme, decreased spontaneous firing rate and firing precision of SNr neurons, demonstrating tonic control of firing rate by H2O2. Elevation of H2O2 in the presence of flufenamic acid revealed an inhibition of tonic firing that was prevented by blockade of ATP-sensitive K+ (KATP) channels with glibenclamide. In contrast to guinea-pig SNr neurons, the dominant effect of H2O2 elevation in mouse SNr GABAergic neurons was hyperpolarization, indicating a species difference in H2O2-dependent regulation. Thus, H2O2 is an endogenous modulator of SNr GABAergic neurons, acting primarily through presumed TRP channels in guinea pig, with additional modulation via KATP channels to regulate SNr output.